2006
DOI: 10.1111/j.1524-4725.2005.31040
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Ultraviolet Light Lip Injury: Beachgoer Awareness about Lip Cancer Risk Factors and Lip Protection Behavior

Abstract: More public education focused on UVL lip protection from UVL is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
8
2
1
Order By: Relevance
“…The only variable significantly related to photoprotection in our study was skin Fitzpatrick phototypes I and II. This finding is in contrast to a survey of 299 beachgoers in Texas concerning skin and specific lip photoprotection; in this study, subjects with Fitzpatrick's phototypes I to III were more likely to use sunscreen for UV skin protection than subjects with types IV to VI, but the use of lip protection was not greater for phototypes I to III [16]. It could be hypothesized that in our study, the most photosensitive patients (Fitzpatrick's phototypes I and II) would be more conscious of the possible harm from the sun and would have increased the use of lip photoprotection.…”
Section: Discussioncontrasting
confidence: 99%
“…The only variable significantly related to photoprotection in our study was skin Fitzpatrick phototypes I and II. This finding is in contrast to a survey of 299 beachgoers in Texas concerning skin and specific lip photoprotection; in this study, subjects with Fitzpatrick's phototypes I to III were more likely to use sunscreen for UV skin protection than subjects with types IV to VI, but the use of lip protection was not greater for phototypes I to III [16]. It could be hypothesized that in our study, the most photosensitive patients (Fitzpatrick's phototypes I and II) would be more conscious of the possible harm from the sun and would have increased the use of lip photoprotection.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data concord with findings from other studies that showed that men are less likely to use sunscreen than women. 19,20 This, along with the high male:female ratios seen for NMSC on subsites of the head, highlights the need for better photoprotection and skin cancer education directed at men.…”
Section: Discussionmentioning
confidence: 99%
“…While a random sample from more localities would be preferable, the method we used is similar to methods used in numerous beach surveys conducted at single beaches. [25][26][27] …”
Section: Limitationsmentioning
confidence: 98%